THE EFFECT OF APPLYING PROBLEM BASED LEARNING ON STUDENTS’ WRITING ABILITY - Lubis, Lollo Rosa; Tanjung, Srimaharani; Kamisah, Kamisah (Institut Pendidikan Tapanuli Selatan, 2025)
The study was conducted to know whether there was a significant effect of applying problem based learning on students’ writing ability. The study used quantitative with design one pretest post test design. Sample of the study consist of 32 students which taken by using total sampling technique. Instrument used writing test. Furthermore, the data was analysis by using descriptive and inferential statistics. Descriptive statistics showed the average of students’ writing ability before applying problem based learning was 54.38 (adequate to fair) and students’ writing ability after applying problem based learning was 84.13 (excellent to good). Based on inferential statistics, pair sample t-test showed Sig (2-tailed) 0.001. This score was less than 0.05 (0.001<0.05). It means, there was a significant effect of applying problem based learning on students’ writing ability. Furthermore, the result of N-Gain formulation showed score 0.6 , this score was medium category. It is concluded problem based learning gave effect to students’ writing ability in medium category